2015
DOI: 10.1007/s11557-015-1064-9
|View full text |Cite
|
Sign up to set email alerts
|

Geoglossum dunense (Ascomycota, Geoglossales): a new species from the Mediterranean islands of Cyprus and Malta

Abstract: Geoglossum dunense, a new species of remarkable morphology, is proposed to accommodate collections from coastal dunes in Cyprus and Malta. Full macro-and micromorphological descriptions are provided, accompanied by molecular data, extensive imagery and a comparison with similar taxa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…He selected an epitype from material collected in Greenland and moved the taxon to the genus Corynetes Hazsl. Lloyd (1916) placed this taxon into the genus Geoglossum and in 1992 Korf and Petersen transferred the species to the genus Thuemenidium. Polyphyly of the genus Thuemenidium was for the first time shown by Ohenoja et al (2010) and subsequently confirmed by Hustad et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…He selected an epitype from material collected in Greenland and moved the taxon to the genus Corynetes Hazsl. Lloyd (1916) placed this taxon into the genus Geoglossum and in 1992 Korf and Petersen transferred the species to the genus Thuemenidium. Polyphyly of the genus Thuemenidium was for the first time shown by Ohenoja et al (2010) and subsequently confirmed by Hustad et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have focused on geomorphological evolution and palaeogeography of coastal dunes in Cyprus. The majority of the studies were focused on the flora and fauna development on the dune formations without emphasizing to the geomorphological and palaeogeographical evolution [26][27][28]. In this context, the aim of this study is to investigate the dunes of the southern coast of Cyprus and furthermore to evaluate the usability of sand dune systems as a tool for the palaeogeographic reconstruction of similar settings in the area of the Eastern Mediterranean.…”
Section: Introductionmentioning
confidence: 99%